Implementation of marketing mix strategy for rubberwood based product by RISDA Melaka / Norizzatina Ruslan - Ruslan, Norizzatina (Faculty of Business and Management, 2008)
Rubberwood has become the most precious asset for our country. Its demand has increasingly from time to time due to high demand for furniture and other products manufacturing. This has seen as an opportunity not to waste by smallholders because this industry will give many benefits to smallholders especially in terms of economic contribution.